Leadership in Middle-Earth : theories and applications for organizations - Urick, Michael J. (Exploring effective leadership practices through popular culture, 2021)
Part of the series Exploring Effective Leadership Practices through Popular Culture, Urick examines mentorship and learning, transformational and servant leadership, culture, bases of power, leader emergence, teams, motivation, and more. Leadership in Middle-Earth explores J.R.R. Tolkien's exemplary leadership and management examples evident in his tales such as 'The Hobbit' and 'The Lord of the Rings', examining mentorship, team dynamics, mindfulness, servant leadership, influence and ethical leadership through solid academic theories and management practices. Readers will become familiar and comfortable with academically supported leadership concepts to adjust their own behaviors, becoming more successful in the process. By examining leadership theories through the context of popular culture, the book encourages readers to think creatively about how they might adjust their own management approach. The series aims to bring examples, theory and methodology of leadership to life by analysing academic concepts through popular culture examples that will appeal to a broad range of readers.